Mechanisms of plasma membrane protein degradation: recycling proteins are degraded more rapidly than those confined to the cell surface. - Hare, J F (1991)
Plasma membrane proteins of intact mouse 3T3 fibroblasts and H4-II-E-C3 hepatoma cells were separated into two groups based on their compartmentation between the cell surface and an intracellular compartment accessible at 20 degrees C but not at 0 degrees C. One group was derivatized at 0 degrees C with sulfosuccinimidyl 2-(biotinamido)ethyl-1,3-dithiopropionate but not at 20 degrees C. The second group was derivatized at 20 degrees C as well as at 0 degrees C. Derivatized proteins were isolated from 35S-labeled cells on streptavidin/agarose and resolved by two-dimensional PAGE. With few exceptions, pulse-chase experiments revealed that those proteins confined exclusively to the cell surface turned over slowly (t1/2, greater than 75 h), while those bimodally compartmentalized between the cell surface and the 20 degrees C accessible compartment were degraded more rapidly (t1/2, less than 31 h). These observations suggest a mechanism to explain the varied metabolic stability of plasma membrane proteins in which the half-life of each protein is determined by the proportion of time spent in the endocytic compartment.